A review of the status and biogeography of the lizard genera Celestus and Diploglossus (Squamata: Anguidae), with description of two new species from Costa Rica - Savage, Jay M (1993)
Sé describe dos especies nuevas de lagartijas diploglosinas. Celeitus hylaiús y Celestus orobius